Temporal dynamics of Linearbandkeramik houses and settlements, and their implications for detecting the environmental impact of early farming. (October 2019) - Meadows, John; Müller-Scheeßel, Nils; Cheben, Ivan; Agerskov Rose, Helene; Furholt, Martin
Long-held ideas concerning early Neolithic Linearbandkeramik (LBK) settlements in central Europe have been thoroughly challenged in recent years, for example, regarding their internal organisation or the use-life of individual houses. These topics have now also been addressed with the help of large radiocarbon ( 14 C) datasets. In the light of this discussion, we present findings of our ongoing research at Vráble in south-western Slovakia. Intensive prospection by fieldwalking, geophysics and sedimentology, complemented by targeted excavations and archaeobotanical investigations, aims to unravel social and temporal relationships between three adjacent LBK settlements. A total of 23 of the c.300 houses revealed by geophysical prospection have been dated. Bayesian chronological modelling of this dataset, comprising 109 14 C ages from 104 samples, indicates that the three LBK settlements at Vráble coexisted, and that overall the LBK settlement lasted for c. 200–300 years. Our results imply a 'short' use-life for individual houses (median c.20–30 y), suggesting that relatively few houses were inhabited simultaneously. Our data suggest that the overall LBK population at Vráble might have increased over the course of occupation, but probably never exceeded 200–300 individuals, based on the number of houses that could have been occupied contemporaneously. We compare the Vráble evidence with Bayesian chronologies for other LBK sites, and discuss the implications of these findings for models of population agglomeration and recognising the environmental impact of early farming communities.